Phytochemical and pharmacological properties of Curcuma aromatica Salisb (wild turmeric) - Nura Muhammad Umar, Thaigarajan Parumasivam, Nafiu Aminu, Seok-Ming Toh (Journal of Applied Pharmaceutical Science, 2020)
Curcuma aromatica Salisb. (C. aromatica) is commonly known as wild turmeric. Curcuma aromatica is an essential herbal plant and it has been extensively used in traditional medicine for centuries. It has been used for the treatment of gastrointestinal ailments, arthritic pain, inflammatory conditions, wounds, skin infections, and insect bites. This article aims to review the phytochemical and pharmacological aspects of C. aromatica and to provide a guide and insight for further studies. Electronic repositories, including Web of Science, Google Scholar, ProQuest, Science Direct, Scopus, and PubMed, were searched until December 2019 to identify studies relating to C. aromatica. A systematic analysis of the literature on pharmacognostical, physicochemical, and nutritional contents, bioactive compounds, and biological activities of C. aromatica was carried out, and ideas for future studies were also coined. A total of 157 articles concerning in vitro or in vivo (or both) researches on C. aromatica have been evaluated. Analyses of the data showed that C. aromatica consists of various classes of compounds, including alkaloids, flavonoids, curcuminoids, tannins, and terpenoids, that formed the bases of its pharmacological activities. The reviewed data also revealed that C. aromatica possessed the pharmacological effect of anticancer, antidiabetic, antioxidant, anti-inflammatory, antimicrobial, antitussive, antiepileptic, analgesic, wound healing, and insect repellent activities. This review has systematically compiled and summarized the literature related to the nutritional values and bioactive compounds, as well as the biological activities of C. aromatica. To the best of our knowledge, this is the most comprehensive review reported on C. aromatica.
Keywords: Pharmacological activity, phytochemical constituents, Curcuma aromatica, Zingiberaceae.